Upaya Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Melalui Penerapan Pendekatan Cooperative Learning Tipe Jigsaw di Kelas III-A SD Negeri 2 Cakrangeara - Asni, Hj (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to find the effectiveness of the application of cooperative learning (CL) Jigsaw type in an effort to improve the activities and learning outcomes of Indonesian, Science, and Mathematics Students of class III.A SD Negeri 2 Cakranegara. The benefit of this research is as references in the implementation of the learning process in the real class for teachers to improve competence in the learning process and to enhance the activities and learning outcomes of learners. This research was conducted in two cycles, and each cycle activity involved; planning, acting, observing and reflecting. The final result of acting in cycle II showed that the teacher observation result got average score (4,69) and the result of observation learners reached average score (4,33). Meanwhile, the learning outcomes of learners achieved an average value (86.39), meaning that the success indicator (> 75.00) has been exceeded. Since the success indicator has been proven in cycle II,then the research is stopped in cycle II.